Tracing Intertextuality Between “Aisyah Istri Rasulullah” and Umdatul Choirot’s Al-Madh Li-‘Aisyah Binti Abi Bakr - Muhammad Ziyad Hubbillah; Ahfa Rahman Syah; Muhammad Faidhur Rahman (Muslim English Literature, 2026)
This study investigates the intertextual dialogue between the viral song "Aisyah Istri Rasulullah" and Umdatul Choirot’s poem, Al-Madh li-‘Aisyah binti Abi Bakr. By applying Julia Kristeva’s theory of intertextuality, the research explores how Choirot’s poem serves as a critical response that effectively reconstructs the representation of Sayyidah ‘Aisyah in the wake of the controversy sparked by the song’s lyrical choices. Utilizing a descriptive qualitative framework, this inquiry navigates the layers of textual space, creative practice, and ideological shifts through a rigorous close reading of both the song’s lyrics and the poem’s verses. The primary dataset, complemented by relevant scholarly literature, serves as the foundation for this comparative analysis. The findings reveal a stark divide in how the two texts engage with the subject. While the song constructs the image of Sayyidah ‘Aisyah primarily through romanticized and physical descriptors—a portrayal that generated significant socio-cultural friction among Muslim audiences—Umdatul Choirot’s poem functions as a deliberate textual transformation. The poem acts as a corrective, repositioning Sayyidah ‘Aisyah not as an object of affection, but as an intellectual, pious, and morally authoritative figure. Ultimately, this study demonstrates that intertextuality operates as more than mere textual interplay; it is a profound exercise in ideological negotiation, deeply rooted in religious ethics, gender perspectives, and the rich traditions of Islamic literature